Functional analysis of tomato MAP65 gene family, highlighting SlMAP65-1’s role in fruit morphogenesis - Peiyu Zhang; Guoning Zhu; Chunjiao Zhang; Hongliang Zhu (Journal of Integrative Agriculture)
The plant growth process is accompanied by dynamic changes in the microtubules, and the rearrangement of microtubules is regulated by diverse microtubule-associated proteins (MAPs). Plant MAP65s have been exhaustively characterized in some species, but the information about MAP65 family members in tomato (Solanum lycopersicum) is limited. In this study, nine SlMAP65 family genes were identified in the tomato genome. Then a systematic analysis that considered the physio-chemical properties, evolution, conserved motifs, domains, gene structure, and cis-regulatory elements of SlMAP65 family members was conducted. The family member SlMAP65-1, which had the highest expression, was knocked out by CRISPR/Cas9. The tomato fruit of slmap65-1 loss of function lines showed an elongated morphology, and the data indicated that SlMAP65-1 is involved in fruit morphogenesis at the early fruit development stage. These results provide new insights for fruit morphogenesis-related research and future functional studies of the SlMAP65 family members in tomato.